2022
DOI: 10.1177/23779608211070154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Guideline on Nurses Performance Regarding Postnatal Care of Mothers and Neonates

Abstract: Background Postnatal periods are very sensitive periods for both the mother and the neonates where morbidity and mortality are high. Post natal care knowledge has significant role in reducing such complications. The research aimed to determine the educational guideline's effect on nurses’ performance regarding mothers and neonates’ postnatal care. Design A quasi-experimental design was decided to fulfil the aim of this study. Setting The study was conducted in the obstetric skill lab of faculty of nursing, Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This might be because training provided to obstetrics care providers related to basic emergency obstetrics and newborn care may enhance basic knowledge and skills about PNC in the management of complications that arise during the postnatal period, especially during the first 24 hours. This was supported by findings from previous studies revealed that training health professionals improve their adherence to available evidence or guidelines,27 and implementation framework combining training, mentoring, demonstrating and redemonstrating of the healthcare providers in the maternity ward on immediate PNC improves the performance of healthcare providers from preprograms to postprogrammes 12 28 29. Interactive and targeted education may be effective in developing clinical practitioner knowledge, skills and attitudes about a guideline’s recommendations 23 30…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This might be because training provided to obstetrics care providers related to basic emergency obstetrics and newborn care may enhance basic knowledge and skills about PNC in the management of complications that arise during the postnatal period, especially during the first 24 hours. This was supported by findings from previous studies revealed that training health professionals improve their adherence to available evidence or guidelines,27 and implementation framework combining training, mentoring, demonstrating and redemonstrating of the healthcare providers in the maternity ward on immediate PNC improves the performance of healthcare providers from preprograms to postprogrammes 12 28 29. Interactive and targeted education may be effective in developing clinical practitioner knowledge, skills and attitudes about a guideline’s recommendations 23 30…”
Section: Discussionmentioning
confidence: 56%
“…This is supported by findings from previous studies, which revealed that besides training, availing evidence-based summaries or guidelines to healthcare providers improves their compliance with immediate PNC guidelines, 27 and maternity nurse practice was improved after the implementation of educational guidelines regarding PNC of mothers and neonates. 29 The use of guidelines ensures healthcare teams have a similar approach to Open access care and most common implementation interventions such as distributing educational material plus educational meetings such as training and other interventions have improved the knowledge and practice of nurses and improved patient outcomes. 30 32 33 Moreover, the odds of good implementation of immediate PNC guidelines by healthcare providers working in a tertiary level hospital (comprehensive specialised and teaching hospital) were 3.85 times higher than those working in a health centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation